The Management of Strategic Change in the Municipal Public Library - Liukinevičienė, Laima; Kuodytė, Kamilė (Socialiniai tyrimai, 2021)
Public libraries, which are undergoing technological and socio-cultural changes, today become centres of socialization of communities, creating social and cultural well-being, therefore, their effective management becomes the object of research. This is also relevant in the implementation of public policy: strategic documents (“Europe 2030”, “Lithuania 2030”), which guide public sector bodies to achieve a sustainable economy, also actualize the ability to anticipate the necessary changes in the organization.In addition to the usual long-term strategic goals (providing high-quality various services, programs, resources to people of all ages; developing existing collections; creating an environment that responds to community needs and promotes creativity), municipal libraries aim to strengthen the institution’s management and develop local communities. Due to COVID-19, the revised strategic plans of public libraries of the Republic of Lithuania have made the accessibility aspect of services even more relevant. Long-term goals testify to the need for strategic change, at the same time raise the problematic questions: what are the essential aspects of science in the management of strategic change in the municipal public library? What is the situation of strategic change management in Lithuanian municipal public libraries? The research aims to practically investigate the situation of strategic change management in Lithuanian municipal public libraries and to discern the aspects to be improved.Based on the scientific literature, we define strategic change as significant fundamental changes in the organization aimed at positive change: to eliminate shortcomings, negative consequences and take on new challenges inherent in the organization’s strategy. They are always linked to the strategic goals of the organization, are changing or touching the entire organization, requiring strategic and change management competencies.The strategic changes implemented in the libraries of the Republic of Lithuania in this decade are more attributable to adaptation or evolution, as there are changes in sustainable growth. According to the hierarchical structural model, strategic administrative (changes in management structures, processes) or strategic functional changes (e.g. changes in personnel, financial management strategy, etc.) are usually initiated in the municipal public libraries themselves. Strategic political and strategic changes in work are mainly driven by politicians. Strategic change requires leadership at all levels of an organization’s governance and is generally seen as a significant factor in increasing employees’ commitment to change.The management of strategic change in libraries as a process has much in common with the management of strategic change in other public sector institutions. Their management in libraries is influenced by external and internal factors, in particular public policy. Among the internal factors for municipal public libraries, the process of managing changes, in general, is important, as it was common practice in Lithuanian municipalities to work in accordance with the municipal cultural policy strategy without developing a separate strategy for the development of their own, separate institution. In the current context of increasing decentralization of governance, it is increasingly the responsibility of libraries to take the initiative and take care of the long-term goals of the organization.The public libraries of two neighbouring municipalities (Akmenė district and Mažeikiai district) were selected for the research, a strategy of mixed methods was applied, combining qualitative research methods (content analysis of documents) and quantitative research methods (total questionnaire survey of both library employees except director and deputy director using apklausa.lt, after receiving participants’ consent via e-mails).Having analysed the strategic plans and activity reports of the years 2011–2021 of public libraries in municipalities of Akmenė district and Mažeikiai district, it was revealed that the most important strategic changes in the recent period correspond to the guidelines of Lithuanian cultural policy (2010) and were mostly technological changes or technological-organizational: related to building reconstructions, renovations; with the digitization of administrative management and services; with the socialization of socially excluded groups, with the increase of digital literacy of communities through education, etc. The documents testify that the public library in Mažeikiai district, during the research, already had its own strategic plan, while the public library in Akmenė district, was developing its first strategy. Different experiences of strategic management have also led to partly different expressions of strategic change management in libraries. The library in Mažeikiai district constantly performs the analysis of external factors, while the library in Akmenė district yet only intends to do so. Among the external factors, the project activities carried out by Martynas Mažvydas National Library of Lithuania, including public libraries, are important in both cases. By strategizing activities, both libraries conduct the performance analysis using SWOT, highlighting similar weaknesses (limited funding for modernization), strengths (systematically training staff, modernized public library infrastructure, strong collaborative relationships with other public and county libraries).Wider cooperation with business is not yet visible. The library in Akmenė district sees the consideration of the needs of stakeholders and the use of social partners’ resources as an opportunity, whereas the library in Mažeikiai district is already planning more active partnership relations, also with Lithuanian and foreign libraries.After conducting the opinion research of the employees of public libraries in Akmenė district and Mažeikiai district, the following most important aspects of the management of strategic changes in the studied municipal public libraries have been revealed:Situation – libraries undergo strategic changes initiated by external institutions through programs and projects; they have experience in implementing strategic change, communicating the results of change; there is no resistance to innovations in libraries; employees begin to be involved in strategic change management through separate sub-processes, while for the time being, managers take the lead in strategic change management; organizations lack a deeper understanding of strategic change, the competencies to initiate them involving the entire library community. Potential – employees would like to be more involved in the management of strategic change: 1) relatively good internal communication about already implemented (mostly project-based) strategic changes is revealed; 2) over 10 percent of employees are already involved in managing strategic change; 3) half of the surveyed employees feel able to offer ideas for innovations and strategic changes, the other 50 percent of employees feel “not invited” to do so; 4) Most staff feel ready to take on good practice from other (including foreign) institutions.This research has confirmed the insights of scholars and cultural strategists that public libraries today are undergoing tremendous change, making long-term perspective knowledge and strategic planning a necessity in every organization. With the growth of decentralization of management as well as the uncertainty due to global changes, in the public sector this is achieved through greater involvement of the community in governance and inter-institutional cooperation. Leadership alone is not enough.This research shows that municipal public libraries have the potential to initiate and manage strategic change themselves, as they have been involved in the implementation of changes initiated by external institutions for 10 years, there is no anti-change attitude in organizations. On the other hand, there is a lack of experience and competencies to anticipate change, initiate change, motivate employees to get involved themselves. This research also raises the debate questions that require broader research:Knowing that municipal public libraries are accustomed to working according to the programs, projects and plans coming from above, the question arises whether the current 2016-2017 legislation on improving library management approved by the Minister of Culture of the Republic of Lithuania is effective and meets today’s challenges; why there is no methodological assistance to public libraries on how to improve their management.What governance structure of municipal public libraries would be conducive to increasing staff involvement in strategic change management? What managerial innovations would increase employee motivation to initiate change?
Keywords: strategic change; strategic change management; municipal public library